Imaging the Deep Spinal Cord Microvascular Structure and Function with High‐Speed NIR‐II Fluorescence Microscopy (Small Methods 8/2022). Issue 8 (17th August 2022) - Zhang, Hequn; Zhu, Liang; Gao, Dave Schwinn; Liu, Yin; Zhang, Jun; Yan, Min; Qian, Jun; Xi, Wang
Abstract : Spinal Cord Imaging In article number 2200155, Yan, Qian, Xi, and co‐workers obtained the deep spinal cord (SC) vascular structure and achieved fast monitoring of indocyanine‐green‐labeled red blood cells up to 100 fps by NIR‐II fluorescent microscopy, which exhibits the great potential of NIR‐II window on SC imaging. The imaging research on SC vasculature is crucial, yet the high scattering tissue greatly affects the improvement of microscopic imaging depth.